Pengembangan Media Mock-Up Berbasis Pendekatan Kontekstual Materi Kenampakan Alam Pada Bangka Belitung Untuk Siswa Kelas V SD - Erdianna; Yurdayanti; Hevitria (JBES (Journal Basic Education Skills), 2025)
Abstract The problem in this study is the need for more varied learning media, especially in the material of Bangka Belitung's natural appearance. This is what causes most of the students to behave passively. This study aims to develop mock-up media based on a contextual approach to the material of Bangka Belitung's natural appearance of grade V elementary school students as a valid, practical, and effective three-dimensional media. This type of research uses Research and Development (R & D) with the ADDIE model, which consists of 5 stages, namely the stages of analysis, design, development, implementation, and evaluation. The subjects of this study consisted of class teachers and 36 grade V students of SDN 38 Pangkalpinang. Data collection techniques and instruments are in the form of observations, interviews, questionnaires, and tests. Data analysis techniques are descriptive, qualitative, and quantitative. Based on the expert validator assessment results, the material obtained 84% (Very Valid), and the media validator obtained 86% (Very Valid). The results of small group trials were obtained at 92% (Very Practical), and those of large group trials were obtained at 94% (Very Practical). Class V teacher response questionnaire obtained 100% (Very Practical). The results of the Paired Samples T-test obtained values of 0.000 < 0.05, where Ha was accepted. This means there are significant differences before and after using mock-up media based on a contextual approach. The study results show that mock-up media based on contextual approaches are valid, practical, and effectively used as learning media.